A New Paradigm of Language Teaching Methods in ESP Instruction - Dewi Surani; Rini Dwi Septiyani (The Study Program of English Education of Palangka Raya University, 2024)
The implementation of the Merdeka curriculum, in language teaching requires a specific method that accommodates the curriculum goal. This writing tries to describe the implementation of some language teaching methods used in the Merdeka Curriculum at a higher level of education in English for specific purposes (ESP) context. This article also give recommendation for lecturers to engage Case Based Learning (CBL), Project Based Learning (PBL), Technology Based Learning (TBL) as language teaching methods in ESP instruction considering their advantages to attain Merdeka curriculum goals.